B. Gentili – C. CatenaCCi – P. Giannini – l. lomiento (edd.), Pindaro: Le Olimpiche, Scrittori Greci e Latini, Fondazione Lorenzo Valla, Milano: Arnoldo Mondadori, 2013, pp. 663, ISBN 978-88-04-62712-8 - Adorjáni, Zsolt (Exemplaria Classica, 2014)
(Reseña)